(C)Sindak an exploratory study on the impact of Sindak on the customer service styles of BeautyMNL's customer service agents - Castillo, Tricia Renee A. (College of Arts and Letters, University of the Philippines Diliman, 2019)
This study discusses how sindak influences the servicing behavior of BeautyMNL's customer service agents during customer service interactions. BeautyMNL is a local e-commerce company that conducts their customer service digitally. For this research, six customer service agents shared their experiences through semi in-depth interviews. The study centered on describing the service providers' realities by exploring the customer service interaction present in BeautyMNL, how sindak was present in the interaction, the effect of sindak on service providers' behaviors, and other factors influencing the customer service agents' customer service styles. All participants revealed that sindak had an impact on the their behavior, however other factors like the company's brand and third-party involvement also affected their responses. BeautyMNL's customer service interactions were non-linear, but evident of the following components: the customer as the source, their complaint/concern as the message, emails and social media as the channels, the customer service agents as the receiver, and the effect as the change in their servicing behavior. Sindak was included in the customer's message, and was identified through the client's hostile language and behavior. Its effect on the interaction was attributed to its capacity to trigger fear and shock, which customers used to control the interaction. The behaviors of BeautyMNL's customer service agents combined Ford's (1999) customer service styles: courteous service, personalized service, and manipulative service. Other findings of the study revealed how digital mediums were more efficient for customer service, and how the service-oriented and customer-centric business landscape implicated the service providers like BeautyMNL's customer service agent.